THE EFFECT OF GENDARUSSIN A ISOLATES OF Justicia gendarussa Burm.f. LEAF IN REVERSE TRANSCRIPTASE IN HIBITION OF HIV TYPE I INVITRO - E. W., Bambang Prajogo; Widiyanti, Prihartini; Nasronudin, Nasronudin; Aksono, Bimo (Institute of Topical Disease Universitas Airlangga, 2015)
Screening has been done to a few extracts from the leaves Justicia gendarussa Burm.f to see the growth rate of the virus from the blood plasma of HIV patients at Dr Soetomo Hospital. It is known that J. gendarussa leaf extract inhibits HIV type 1 reverse transcriptase. In addition, its main content is gendarussin A, besides gendarussin B, JGF1, JGF2 and JGF3, which have just identified. At the beginning, extraction and fractionation were performed with 3 models that highlight the absolute methanol, 70% methanol and 70% ethanol with the release of alkaloids. Furthermore, samples of each fraction were incubated in plasma of HIV patients with a titer of 3.6 10^6 copies for 1 h in concentrations of 1.64 ppm, 4.1 ppm, 8.2 ppm, 16.4 ppm and 41.0 ppm. After incubation, examination was performed by using Nucli sens a machine, which is a combination of PCR and Elisa, thus avoiding direct contact with the highly pathogenic virus. The result showed that the activity sequence from the most potential to the weak, among others, was 1.64 ppm >4.1 ppm > 8.2 ppm > 16.4 ppm > 41.0 ppm, each with barriers value of 0.62 10^6, 1.4 10^6, 1.6 10^6, 2.4 10 cells/ml. In conclusion, highest anti-HIV activity comes from the concentration of gendarussin A isolate at 1.64 ppm. Furthermore, after linearregression of y = -3.063 x + 81.37 was done, the IC50 of 10.24 ppm was obtained.